The AdVance™ male sling: does it stand the test of time?. (4th March 2021) - Rizvi, Ishtiakul G.; Ravindra, Pravisha; Pipe, Michelle; Sohawon, Ridwaan; King, Thomas; Belal, Mohammed
Abstract: Introduction: There is minimal data published on the longevity of the transobturator retrobulbar male sling (AdVance™). We aimed to determine the efficacy, the complication rate and need for salvage SUI surgery in the medium to long term for male sling insertion. Materials and methods: We performed a retrospective review of all patients undergoing male sling insertion at a single centre between 2009 and 2018. Data on patient demographics, pre and post-operative International Consultation on Continence Questionnaire – Urinary Incontinence (Short Form) (ICIQ-UI(SF)) scores and 24 h pad usage were collected. Success was calculated as a combination of the cured rate (0–1 security pad use) and the improved rate (>50% reduction in pad usage). Data was also collected on complications, patient satisfaction as well as need for further SUI surgery. Results: A total of 91 patients underwent male sling insertion in the period specified; median follow up was 69 months. Success rates at 3 months in mild SUI, moderate SUI and severe SUI groups were 96, 86 and 80%, respectively. In the medium to long term, this drops to 65, 62 and 47%, respectively. The overall rate of artificial urinary sphincter (AUS) implantation was 15%. Common complications included groin pain (3%), infection (3%), urinary retention (10%) and de novo overactive bladder (OAB) (11%). The only factor predicting success or failure was pre-operative ICIQ-UI(SF) score. Conclusions: AdVance™ male sling success rates deteriorate from 89% at 3 months to 61% at 5 years. The risk of complications is low and, for the most part, transient. Sling insertion remains a reasonable treatment option for male patients suffering with stress urinary incontinence (SUI).